Constructing Eh-pH Diagrams of Plutonium by Using Its Thermodynamics Properties - Sahat Simbolon (BATAN, 2001)
ABSTRACT Eh-pH diagrams of Plutonium under standard temperature and pressure (STP) condition are constructed. The stability domain of water is described based on redox reaction of water with oxygen and hydrogen. Two pair lines which are almost paralel to each other are found. Redox reaction of Plutonium poduces four Nerst equations; each equation is represented by one line and one vertical line as a result of non redox reaction. The length of each line depends on other lines. There are two pair lines which are overlapped each other if the concentration of each species equals to 10-9 M. It is also described Eh-pH diagrams for Plutonium with different concentrations. ABSTRAK Telah dibuat diagram Eh-pH Plutonium di dalam udara dengan tekanan dan suhu standar. Daerah stabilitas air ditentukan berdasarkan reaksi redoks air - oksigen dan air - hidrogen. Didapatkan dua pasang garis lurus yang hampir sejajar satu sama lain. Reaksi redoks dari Plutonium menghasilkan 4 persamaan Nerst, tiap persamaan digambarkan dalam bentuk garis dan satu garis tegak akibat reaksi non redoks. Panjang setiap garis sangat bergantung pada garis - garis lainnya. Didapatkan dua pasangan garis yang saling tumpang - tindih kalau konsentrasi masing-masing spesiesnya sama dengan 10-9 M. Digambarkan juga Ehl-pH diagram untuk konsentrasi spesies Plutonium yang tidak sama.